Fiber optic quench detection for large-scale HTS magnets demonstrated on VIPER cable during high-fidelity testing at the SULTAN facility. (4th February 2021) - Salazar, Erica E; Badcock, Rodney A; Bajko, Marta; Castaldo, Bernardo; Davies, Mike; Estrada, Jose; Fry, Vincent; Gonzales, Jofferson T; Michael, Philip C; Segal, Michael; Vieira, Rui F; Hartwig, Zachary S
Abstract: Fiber-optic thermometry has the potential to provide rapid and reliable quench detection for emerging large-scale, high-field superconducting magnets fabricated with high-temperature-superconductor (HTS) cables. Developing non-voltage-based quench detection schemes, such as fiber Bragg grating (FBG) technology, are particularly important for applications such as magnetic fusion devices where a high degree of induced electromagnetic noise impose significant challenges on traditional voltage-based quench detection methods. To this end, two fiber optic quench detection techniques—FBG and ultra-long FBG (ULFBG)—were incorporated into two vacuum pressure impregnated, insulated, partially transposed, extruded, and roll-formed (VIPER) high-current HTS cables and tested in the SULTAN facility, which provides high-fidelity operating conditions to large-scale superconducting magnets. During surface heater induced quench-like events under a variety of operating conditions, FBG and ULFBG demonstrated strong signal-to-noise ratios (SNRs) ranging from 4 to 32 and measured single-digit temperature excursions; both the SNR and temperature sensitivity increase with temperature. Fiber thermal response times ranged between effectively instantaneous to a few seconds depending on the operating temperature. Strain sensitivity dominates the thermal sensitivity in the conditions achievable at SULTAN; however, measurements at higher quench evolution temperatures, coupled to future work to increase the thermal-to-strain signal, show promise for quench detection capability in full-scale magnets where temperature and strain may occur simultaneously. Overall, FBG and ULFBG were proven capable to quickly and reliably detect small temperature disturbances which induced quench initiation events for high current VIPER HTS conductors in realistic operating conditions, motivating further work to develop FBG and ULFGB quench detection systems for full-scale HTS magnets.